Historical evolution, hotspots, and trends in tendon tissue engineering: A bibliometric analysis - Wenlong Hou; Wenwen Liu; Mengtian Tan; Jiaxu Fang; Keye Cao; Xincheng Du; Haijun Zhang (Regenerative Therapy)
Introduction: As a significant branch of tissue engineering, tendon tissue engineering has developed rapidly, driven by advancements in new technologies and the refinement of medical theories. This study summarizes its development by analyzing historical evolution, research hotspots, and future trends to reveal core research directions and potential pathways. Methods: Based on literature from WoS CC (1991–2024) and analyzed using VOSviewer, CiteSpace, and Bibliometrix, the study evaluates publication trends and research patterns. Results: Findings show continuous growth in annual publications. The United States and China are key contributors with close collaboration. Chang James is the most prolific author, and stable research teams have emerged, though inter-team cooperation remains limited. Acta Biomaterialia publishes the most papers in this field, characterized by interdisciplinary integration. Key research focuses include scaffolds, seed cells, and rotator cuff injuries. Frontiers involve ideal scaffold construction, tendon adhesion prevention, and regeneration strategies. Future directions emphasize novel biomaterials, tendon-bone interface healing, innovative seed cell cultivation, tendon growth microenvironment construction, and clinical translation of research outcomes. Conclusion: This bibliometric analysis reveals the core research directions and potential pathways in tendon tissue engineering, providing a reference for future studies.